GPU ACCELERATED MKIDS READOUT SYSTEM - Nassipkaliyev, Azamat (Nazarbayev University School of Engineering and Digital Sciences, 2024)
Microwave kinetic inductance detectors or MKIDs, for short, are the devices used for photon detectance. They have a lot of advantages over the other devices like their readout precision and a relatively low readout noise. However, what really makes them irreplaceable is the capability of utilizing the frequencydomain multiplexing over the array of many pixels. The aim of this project is to present a new readout system that utilizes the high computational capabilites of GPU designed for MKIDs and prove its reliability